2008
DOI: 10.3800/pbr.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enumeration of sulphate-reducing bacteria from aquatic environments using real-time PCR

Abstract: Abstract:We describe a rapid and simple enumeration method for sulphate-reducing bacteria (SRB) from aquatic environments using a quantitative real-time PCR (qPCR) in combination with a rapid DNA isolation method. Enumeration of SRB in the sediment and water samples was performed by quantifying the copy number of the dsrA gene coding for the a-subunit of the dissimilatory sulphite reductase using real-time PCR with the SYBR Green I assay. Using dsrA-specific primers, we demonstrated that quantification of SRB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 21 publications
1
31
0
5
Order By: Relevance
“…In the only other study specifically investigating dsrA genes from BBD lesions, Barneah et al (2007) similarly observed sequences closely related to Desulfovibrio species and retrieved no representatives from other genera of SRB, implying the dominance of Desulfovibrio in BBD lesions. Studies investigating the microbial diversity of BBD lesions from different geographical regions using 16S rRNA gene profiling techniques have also identified Desulfovibrio affiliated sequences as constituents of the BBD mat (Cooney et al, 2002;Frias-Lopez et al, 2002, 2004 A quantitative qRT-PCR assay targeting the dsrA gene with primers DSR1-F þ and DSR-R, was adapted from Kondo et al (2008) and LeLoup et al (2007). The qPCR assay was modified through the use of the TaqMan chemistry (Applied Biosystems, Foster City, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the only other study specifically investigating dsrA genes from BBD lesions, Barneah et al (2007) similarly observed sequences closely related to Desulfovibrio species and retrieved no representatives from other genera of SRB, implying the dominance of Desulfovibrio in BBD lesions. Studies investigating the microbial diversity of BBD lesions from different geographical regions using 16S rRNA gene profiling techniques have also identified Desulfovibrio affiliated sequences as constituents of the BBD mat (Cooney et al, 2002;Frias-Lopez et al, 2002, 2004 A quantitative qRT-PCR assay targeting the dsrA gene with primers DSR1-F þ and DSR-R, was adapted from Kondo et al (2008) and LeLoup et al (2007). The qPCR assay was modified through the use of the TaqMan chemistry (Applied Biosystems, Foster City, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic capability of dissimilatory sulfate reduction is widely distributed within both bacterial and archeal phyla and the enzyme responsible (dissimilatory sulfite reductase; DSR) is highly conserved and ubiquitous in all known sulfate-reducing prokaryotes and, therefore, ideal for assessing the diversity of these populations within environmental samples (Wagner et al, 1998(Wagner et al, , 2005Leloup et al, 2007;Kondo et al, 2008). This study modified an established quantitative real-time PCR (RT-PCR) approach, targeting the gene coding for the a-subunit of the DSR gene (dsrA) (Leloup et al, 2007;Kondo et al, 2008) to assess both the diversity and relative abundance of SRB within microbial samples collected from CP, intermediate stages (IM) and BBD coral disease lesions. Owing to the variability in bacterial population diversity and sampled biomass within individual coral lesions, the SRB population was determined as a percentage of the total bacterial population by including a quantitative RT-PCR assay targeting the bacterial 16S rRNA gene (Nadkarni et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Each reaction contained 1 µL of brackish or freshwater wetland DNA template and was conducted using the PerfeCTa SYBR Green FastMix (Quanta BioSciences). For the mcrA qPCR, primer details and thermocycling conditions in West et al (2012) were replicated except that we employed a fluorescent detection step at 78 • C for 20 s. For the dsrA qPCR primer, details and thermocycling conditions in Kondo et al (2008) were replicated. Melting curves for both mcrA and dsrA were run to ensure the absence of non-specific amplification.…”
Section: Microbial Analysesmentioning
confidence: 99%
“…We amplified mcrA using primers detailed in Luton et al (2002) and thermocycling conditions in West et al (2012), and dsrA by replicating primer details and thermocycling conditions in Kondo et al (2008). After amplification, we used gel electrophoresis and an Invitrogen PureLink Quick Gel Extraction Kit (Invitrogen, Carlsbad, CA, USA) to isolate the mcrA and dsrA amplicons.…”
Section: Microbial Analysesmentioning
confidence: 99%
“…After transportation to the laboratory, within a few hours of sampling, a 50-mL aliquot was filtered through a sterile polycarbonate membrane filter (0.2 µm; Toyo Roshi Kaisha, Tokyo, Japan) to collect the microbial biomass for subsequent nucleic acid purification. Nucleic acids were extracted from the filtered samples using a FastDNA Spin Kit as described previously (16).…”
Section: Sample Collection and Dna Extractionmentioning
confidence: 99%